Social forestry: Malaysia experience / Aminuddin Mohamad - Mohamad, Aminuddin (2013)
Coastal line is an important feature to one's country. The very long coastal line of Malaysia is subjected to open sea and waves hitting the coastline. Some portion of the coastline is affected and damaged except for those having Mangrove forests along it. Some of the coastline in the states of Kedah and Johor have been destroyed and retreat inland. Steps have been taken by the Forestry Department Peninsular Malaysia to plant species of Mangrove together with other coastal species like Casuarina equisetifolia in order to reduce the impact of the damage. This paper tends to highlight the long term social forestry program undertaken by the Forestry Department in order to reduce the damage to the coastline.